High Leaf Respiration Rates May Limit the Success of White Spruce Saplings Growing in the Kampfzone at the Arctic Treeline - Griffin, Kevin L.; Schmiege, Stephanie C.; Bruner, Sarah G.; Boelman, Natalie T.; Vierling, Lee A.; Eitel, Jan U. H. (Frontiers in Plant Science, 2021)
Arctic Treeline is the transition from the boreal forest to the treeless tundra and may be determined by growing season temperatures. The physiological mechanisms involved in determining the relationship between the physical and biological environment and the location of treeline are not fully understood. In Northern Alaska we studied the relationship between temperature and leaf respiration in 36 white spruce (Picea glauca) trees, sampling both the upper and lower canopy, to test two research hypotheses (H0). The first H01 is that canopy position will not influence leaf respiration. The associated alternative hypothesis (HA) is that the upper canopy leaves which are more directly coupled to the atmosphere will experience more challenging environmental conditions and thus have higher respiration rates to facilitate metabolic function. The second H02 is that tree size will not influence leaf respiration. The associated HA is that saplings (stems that are 5-10 cm DBH (diameter at breast height)) will have higher respiration rates than trees (stems ≥ 10 cm DBH) since saplings represent the transition from seedlings growing in the more favorable aerodynamic boundary layer, to trees which are fully coupled to the atmosphere but of sufficient size to persist. Respiration did not change with canopy position, however respiration at 25°C was 42% higher in saplings compared to trees (3.43 ± 0.19 vs. 2.41 ± 0.14 micro mol m-2 s-1). Furthermore, there were significant differences in the temperature response of respiration, and seedlings reached their maximum respiration rates at 59°C, more than two degrees higher than trees. Our results demonstrate that the respiratory characteristics of white spruce saplings at treeline are extreme, imposing a significant carbon cost that may contribute to their lack of perseverance beyond treeline. In the absence of thermal acclimation, the rate of leaf respiration could increase by 57% by the end of the century, posing further challenges to the ecology of this massive ecotone.